Corresponding Risk Factors for Psychosocial Disorders in Children with Congenital Adrenal Hyperplasia during the COVID-19 Pandemic - Muhammad Faizi, - (Skopje, 2022)
BACKGROUND: Congenital adrenal hyperplasia (CAH) is a chronic disease that requires lifelong medical therapy; thus, it has become a psychosocial stressor associated with mental, emotional, and behavioral disorders in children and adolescents. The COVID-19 pandemic is also an additional stressor in addition to chronic physical illness, biological factors, cognitive factors, environment, age, parental education, parents’ occupations, and family income. AIM: Thus, in this study, we aim to analyze the risk factors for psychosocial disorders among children with CAH. METHODS: This research was a cross-sectional study conducted from January to April 2021 at the Pediatric Endocrinology Outpatient Clinic in Dr. Soetomo General Hospital in Surabaya. Data were collected through interviews, questionnaires, and medical records and then analyzed through univariate and bivariate analyzes using Chi-square test (Fisher’s exact test). RESULTS: In total, 30 children were enrolled in this study, among which 8 (26.7%) had emotional disorders, 5 (16.7%) had behavioral disorders, and most (83.3%) did not have hyperactivity/attention disorders. It was found that 8 children (26.7%) had problems with peer relationships, whereas most (83.3%) did not experience prosocial disorders. Family income (p = 0.032, CI = 95%) and hyperactivity (p = 0.019, CI = 95%) were found to be significantly correlated to conduct problems. CONCLUSIONS: Family income, behavioral disorders, and hyperactivity/attention disorders were identified as risk factors for psychosocial disorders in children with CAH during the COVID-19 pandemic